PENGARUH BRAND SIGNATURE DAN BRAND LOGO TERHADAP BRAND REPUTATION - Afifatul Khoiroh; Dea Elvira; Lingga Yuliana (LP2M Universitas Bina Bangsa, 2023)
This study aims to analyze brand signature and brand logo affect brand reputation. This research provides novelty because there has not been found before a correlation between brand signature and brand logo on brand reputation either simultaneously or partially. Purposive sampling is the sampling method used in this study, using quantitative descriptive methodology. Participants in this study used Ms Glow skincare products to become respondents spread across Indonesia. Respondents in this survey are men and women aged 15-55 years. Information with primary data as many as 106 respondents who used the Ms Glow brand and received questionnaires distributed using Google Form. The data analysis technique used in this test is Partial Least Square (PLS). This study used SmartPLS tool version 3.3.9. The results showed that there is an influence between brand signature on brand reputation as the first hypothesis. The second hypothesis suggests that brand logos influence brand reputation.